Marfan Syndrome and Physical Exercise: a Perspective Based on Recent Evidence - Jorge Luis Abreus Mora; Antonio Héctor Suárez del Villar Soria; Rafael Rodríguez del Rey Medina (Revista Finlay, 2025)
Marfan syndrome is a genetic disease that compromises different systems. Physical restrictions to avoid complications can affect patients' quality of life. Low-intensity aerobic exercises and activities such as yoga and pilates show significant benefits including better blood pressure control, muscle strengthening and emotional well-being, however, high-intensity exercise or contact sports are contraindicated due to the risk of complications cardiovascular, musculoskeletal injuries and eye problems. Medical supervision and a personalized approach to patient care are essential. Adapted physical exercise improves quality of life in patients with Marfan syndrome if performed under medical supervision and with personalized adjustments. Future research should focus on specific exercise protocols and continuous monitoring strategies.